COMPETENCY OF SAFETY AND HEALTH COMMITTEES: CURRENT REALITIES AND THE WAY FORWARD - Farouk, Ummu Kolsome (PEOPLE: International Journal of Social Sciences, 2016)
The purpose of this paper is to discover the state of competency of occupational safety and health committees (OSHCs) and its influence on effective OSHCs in Malaysia. Using survey data from 231 manufacturing firms, the study empirically examined the influence of both competency of OSHCs and that of scope of OSHCs on the perceived effectiveness of OSHCs, and the relationships among these three variables. Respondents of the survey method, who were members of OSHCs, perceived all three variables at the medium level. Findings also confirm that scope of OSHCs partially mediates the relationship between the other two variables. This paper provides suggestions on how competency of OSHCs can be improved.